2022
DOI: 10.1038/s42003-022-03537-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular immune features of aged patients with severe COVID-19 pneumonia

Abstract: Aging is a major risk factor for developing severe COVID-19, but few detailed data are available concerning immunological changes after infection in aged individuals. Here we describe main immune characteristics in 31 patients with severe SARS-CoV-2 infection who were >70 years old, compared to 33 subjects <60 years of age. Differences in plasma levels of 62 cytokines, landscape of peripheral blood mononuclear cells, T cell repertoire, transcriptome of central memory CD4+ T cells, specific antibodies are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…Despite this, it is not possible to confirm if the IL-6 was elevated due to the severity of the disease. The severe group has a higher median age ( p = 0.005), that can contribute to elavated IL-6 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, it is not possible to confirm if the IL-6 was elevated due to the severity of the disease. The severe group has a higher median age ( p = 0.005), that can contribute to elavated IL-6 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other respiratory viral infections, the immune response to SARS-CoV-2 is characterized by robust production of proinflammatory cytokines but diminished interferon Type I and III responses [ 7 , 8 ]. Molecular and cellular immune features of 31 patients aged > 70 years with severe COVID-19 pneumonia have suggested that inflammation, coupled with the inability to have a proper anti-viral response, could aggravate disease severity and the worst clinical outcome [ 9 ]. Comparative host transcriptome analysis across distant coronavirus genres showed 23 pathways and 21 Differentially expressed genes (DEGs) across ten immune response-associated pathways were shared by these viruses, and these DEGs could be utilized as specific targets for novel coronavirus treatments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the immune response mounted against Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection is crucial to understanding and predicting short- and long-term protection. Both innate and adaptive immunity has been well described during severe cases as well as in recovered patients [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] and it has been reported that an integrated response can limit COVID-19 disease severity [ 11 ]. Developing SARS-CoV-2 antigen-specific CD4+ and CD8+ T cells besides antibodies is crucial to prevent severe outcomes and protect against reinfections [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%